Geologi dan Mineralisasi Uranium Sektor Nyaan Mahakam Hulu Kalimantan Timur - Sukadana, I Gde (BRIN Publishing, 2012)
Nyaan Sector covered 0.5 km2 area. The aim of research is to understand the geological setting, mineralization and potency of uranium in Nyaan Sector. The research activities involved topography measurement, soil radioactivity measurement by grid of 20x20 m2, stratigraphic and detailed geological structure observation, the making of peels at any anomaly area and radioactivity anomaly area. There are 3 (three) significant radiometric anomaly locations at Nyaan Sector. They are anomaly Sungai Marta, Marta Hulu and Aloha with radiometric value ranges from 8000 c/s to > 15000 c/s with background value of 100 c/s. In these areas, the making of peels, trench and test pit were conducted by sampling mineralization using systematic channel sampling system by the sum of 15 channels sampling and 8 chieps sampling. The petrography and mineralogy analysis exhibited that mineralization of pitchblende, monazite, autunite were associated with bornite, chalcocite, chalcopyrite, lolingite, pyrite, sphalerite, ilmenite, limonite, magnetite, marchasite, rutile, malnicovite, hematite and iron oxide. Results of geochemical analysis for total uranium content in the rocks ranged between 345 to 11.425 ppm of uranium.